A Preliminary Study Toward Development of a Tool to Help Detect Accounting Improprieties in Japan - Uchida, Yasuo; Tagawa, Shinya; Matsuno, Seigo; Sakamoto, Makoto (International Review of Management and Marketing, 2019)
Japan in recent years has seen a succession of cases of accounting improprieties. For example, a study by Tokyo Shoko Research shows that 57 publicly traded companies disclosed improper accounting or bookkeeping during 2016 (January–December), reflecting a rapid increase of 2.2 times from the 25 companies that did so in 2008. The increase in such cases among major firms whose shares are traded on the First Section of the Tokyo Stock Exchange stands out in particular. Factors that have been identified as possibly being behind this rapid increase include compliance failures, lack of knowledge, demanding excessively tough quotas from employees, and enhancement of auditing systems. The cases of accounting improprieties at Olympus and Toshiba in particular involve aspects that could be described as issues involving society as a whole. In addition, the fact that auditors proved unable to detect these cases of accounting improprieties and other issues at the companies they audited has shaken trust in auditing itself. Accordingly, as a preliminary study toward the development of a tool to help detect accounting improprieties in Japan, the author will attempt to detect the possibility of accounting improprieties from the content of the publicly released securities reports of the companies involved in these cases. Specifically, the author developed a simple automated tool to extract and graph cash-flow information from the securities reports available for downloading from EDINET and then considered whether these graphs could be used to identify signs of accounting improprieties. Keywords: Accounting fraud, EDINET, Detection support JEL Classifications: M1, M4 DOI: https://doi.org/10.32479/irmm.7249